Automated Sample Storage in Biobanking to Enhance Translational Research: The Bumpy Road to Implementation - Linsen, Loes; Van Landuyt, Kristel; Ectors, Nadine (Frontiers in Medicine, 2020)
The low reproducibility of biomarker research is a major holdback for the translation of research results to the bedside. Sample integrity has been identified as a key factor that contributes to improved reproducibility. The key mission of biobanks is to ensure that all activities and materials are managed according to standardized procedures and best practices to ensure and preserve sample integrity. When handling large numbers of biospecimens automation of sample handling and storage is often the method of choice to maintain and improve sample integrity. In December 2013, the centralized Biobank of the University Hospitals and Catholic University Leuven (UZ KU Leuven) decided to implement automated systems for sample storage and retrieval, one for storage at -20°C and one for storage at -80°C. Here we describe the extensive process of installation, acceptance, validation and implementation of these two systems. Overall it took about four years to effectively take the systems into production. Multiple issues resulted in the delayed implementation, with labware change, quality of the initial installation and misunderstanding of biobank concerns being the most impacting. Significant effort in terms of time and resources from both the automated store supplier as well as the biobank itself was needed to achieve a successful implementation. Within 15 months of actual integration in the biobank workflow, over 50k samples were inputted into the systems. Actual hands-on sample handling and retrieval times were substantially reduced, although this implied the shift of dedicated personnel time from the researchers’ labs to the biobank. With the successful implementation of automated frozen sample storage systems, the centralized UZ KU Leuven Biobank is now also able to efficiently support large-scale translational research.